Mindre demokrati, mindre fred? En kvalitativ fallstudie av sambandet mellan democratic backsliding och positiv fred i Tjeckien - Glimbrand Malmros,Matilda (2024)
During the last decade, democratic backsliding has become a worrying phenomenon around the globe. However, despite the extensive attention paid to the phenomenon in the literature, surprisingly little has been said about its potential impact on peace, and particularly positive peace. In order to contribute to this research gap, this essay seeks to investigate to what extent there is a correlation between democratic backsliding and decreased positive peace. To answer the line of question, a qualitative case study has been conducted on Czechia, primarily building on comprehensive quantitative data. Czechia presents an interesting case, as previous research has mainly focused on Hungary and Poland, leaving the case of Czechia inadequately investigated. Furthermore, the study also seeks to identify potential trends and patterns concerning democratic backsliding and decreased positive peace in Central and Eastern Europe. Based on the results, it can be stated that it is somewhat difficult to draw any validated conclusions, as well as it is not possible to identify a clear correlation between democratic backsliding and decreased positive peace in Czechia. The absence of correlation challenges the conventional perception of positive peace and democracy as closely linked, suggesting a reevaluation of the assumed relationship between the two.
Keywords: democratic backsliding; Central and Eastern Europe; Czechia; positive peace; Positive Peace Index